The Potential of Palm Oil as An Economic Recovery in Central Kalimantan in The Era of A Pandemic: Typology Klassen Analysis - Annisa Nur Fadhilah; Lita Jowanti; Atika Kautsar Ilafi (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Palm oil is one of Central Kalimantan's leading commodities. With a plantation area of almost two million hectares. Central Kalimantan is capable of producing up to eight million tons of palm oil annually. During the pandemic, Central Kalimantan's economy experienced the deepest contraction of up to 3.17 percent due to restrictive policies to prevent the spread of the virus. According to Statistics of Indonesia, the agriculture, forestry, and fisheries sectors are the most resilient sectors because they can grow positively amid a pandemic. The palm oil commodity could be a solution for boosting the economy of Central Kalimantan through appropriate management strategies. One strategy in recovering from the impact of the pandemic is through Small and Medium Enterprise's innovation. Based on the Klassen Typology analysis, Pulang Pisau Regency has the biggest potential for developing oil palm SMEs (quadrant I). In addition, Palangka Raya City and Kapuas Regency are in quadrant IV, which means they have the highest number of SMEs. However, their economic growth has contracted.